A review of phage mediated antibacterial applications. Issue 1 (1st January 2021) - Ssekatawa, Kenneth; Byarugaba, Denis K.; Kato, Charles D.; Wampande, Eddie M.; Ejobi, Francis; Tweyongyere, Robert; Nakavuma, Jesca L.
ABSTRACT: Background : For over a decade, resistance to newly synthesized antibiotics has been observed worldwide. The challenge of antibiotic resistance has led to several pharmaceutical companies to abandon the synthesis of new drugs in fear of bacteria developing resistance in a short period hence limiting initial investment return. To this effect, alternative approaches such as the use of bacteriophages to treat bacterial infections are being explored. This review explores the recent advances in phage-mediated antibacterial applications and their limitations. Methods : We conducted a comprehensive literature search of PubMed, Lib Hub and Google Scholar databases from January 2019 to November 2019. The search key words used were the application of bacteriophages to inhibit bacterial growth and human phage therapy to extract full-text research articles and proceedings from International Conferences published only in English. Results : The search generated 709 articles of which 95 full-text research articles fulfilled the inclusion guidelines. Transmission Electron Microscopy morphological characterization conducted in 23 studies registered Myoviruses, Siphoviruses, Podoviruses, and Cytoviruses phage families while molecular characterization revealed that some phages were not safe to use as they harbored undesirable genes. All in vivo phage therapy studies in humans and model animals against multidrug-resistant (MDR) bacterial infection provided 100% protection. Ex vivo and in vitro phage therapy experiments exhibited overwhelming results as they registered high efficacies of up to 100% against MDR clinical isolates. Phage-mediated bio-preservation of foods and beverages and bio-sanitization of surfaces were highly successful with bacterial growth suppression of up to 100%. Phage endolysins revealed efficacies statistically comparable to those of phages and restored normal ethanol production by completely eradicating lactic acid bacteria in ethanol fermenters. Furthermore, the average multiplicity of infection was highest in ex vivo phage therapy (557, 291.8) followed by in vivo (155, 612.4) and in vitro (434.5).